Combined Anterior and Posterior vs Isolated Posterior Facet Fixation for Subtalar Arthrodesis: A Proportional Meta-Analysis and Systematic Review of the Literature - Antonio Izzo MD; Giovanni Manzi MD; Martina D'Agostino MD; Massimo Mariconda MD; Shelain Patel FRCS (Tr&Orth); Alessio Bernasconi MD, PhD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Other Introduction/Purpose: Subtalar arthrodesis (SA) is a common procedure to treat end-stage subtalar osteoarthritis. We set out in order to determine whether a combined direct fixation of both anterior and posterior facets during SA might influence union and complications compared to isolated fixation of the posterior facet. Our hypothesis was that a combined fixation increases the union rate and reduces the complication rate. Methods: In this PRISMA-compliant PROSPERO-registered systematic review, we included studies reporting data after SA stabilized with screws in adults. The characteristics of the cohort, study design, surgical details, nonunion and complication rate at the longest follow-up were recorded. The modified Coleman Methodology Score (mCMS) was applied to appraise the quality of studies. Two groups were compared: an ANT/POST group (screws positioned both in the anterior and posterior facet) and an ONLY POST group (isolated posterior facet fixation). Results: Eighteen series (685 feet: ANT/POST=96, ONLY POST=589) were selected. The median follow-up was 28 months (IQR, 12-42). The pooled proportion showed a similar nonunion rate (6% vs 10%;p=0.46) and complication rate (14% vs 19%,p=0.47) in the ANT/POST group as compared to the ONLY POST group. The pooled proportion of reoperation was not different either (ANT/POST: 7% vs ONLY POST: 10%,p=0.37). Kernel regression suggested a correlation between the proportion of open/arthroscopic procedures and the nonunion rate (p=0.025) with a median nonunion rate at 10.9% and 5.9% for open and arthroscopic procedures, respectively. Mean CMS was 40.4 points (poor quality). Conclusion: This proportional meta-analysis suggested that a combined direct fixation of anterior and posterior facets during subtalar arthrodesis does not significantly influence the risk of nonunion nor affects the risk of complication and reoperation as compared to isolated posterior facet fixation.